Factors Influencing Online Buying Intention among Royal Malaysian Police (RMP) Officers - Mohd Nazri, Sofia Anis Anisha; Othman, Abdul Kadir (Information Management and Business Review, 2023)
Online buying has become a norm in Malaysia after the COVID-19 pandemic. It is one of the measures to cope with the rapid spread of the virus. Royal Malaysian Police (RMP) staff is not left behind in following the current trend. The present study is intended to determine the factors that influence them to engage in online buying although they are very busy ensuring public safety. Data was collected using online surveys distributed conveniently to the staff. After the lapse of the allocated data collection period, 150 responses were received and analyzed. Out of five factors that have been selected as the independent variables, only two are significant in influencing online buying intention among the RMP staff: attitude and perceived usefulness. Perceived ease of use, subjective norms, and perceived behavioral control did not significantly influence the online buying intention of RMP officers. The findings show that only those with the right attitude towards online buying and those who find online buying beneficial will pursue online purchases.